Wet-chemical synthesis of noble metal-based nanostructures with controlled phase - Yun, Qinbai (Nanyang Technological University, 2020)
Phase engineering of nanomaterials has been proven a promising approach to alter their physicochemical properties and functions, as the atomic arrangements and electronic structures can be tuned in different phases. For noble metal nanostructures, the most widely studied catalysts, they normally crystallize in face-centered cubic (fcc) or hexagonal close packed (hcp) phases. Besides crystalline phase, noble metals can also exist in amorphous phase. The abundant low-coordinated atoms in amorphous noble metals are thought to be capable to enhance their catalytic performance. However, the strong metallic bonds between adjacent metal atoms make it difficult to alter the phase of noble metal-based nanostructures. Wet-chemical method has been proven effective in modulating the size, morphology and composition of the noble metal-based nanostructures during the past decades. Nevertheless, it still remains a great challenge to tune the phase of noble metal-based nanostructures by using this method. This thesis aims to explore the wet-chemical methods to prepare noble metal-based nanostructures with controlled phase, and investigate the structure-performance relationship by assessing the catalytic performance of noble metal-based nanostructures with different phases. Specifically, the following works will be discussed: First, a facile wet-chemical strategy has been proposed to produce a novel class of PdM (M=Zn, Cd, ZnCd) nanosheets with thickness less than 5 nm. The obtained PdM nanosheets crystallize in a face-centered tetragonal (fct) phase, different from the conventional fcc phase of Pd. The reaction temperature has been proven a key factor contributing to the formation of the fct phase. When utilized as catalysts for ethanol oxidation reaction, the obtained fct PdZn nanosheets exhibit much higher mass activity and better stability than the commercial Pd black and fcc Pd nanosheets. Second, a one-pot wet-chemical method has been developed to prepare amorphous Rh nanoparticles with uniform size distribution. By tuning the reaction parameters, crystalline Rh nanoparticles with similar size and surface ligands can also be synthesized. Moreover, this synthetic strategy is able to be extended to prepare amorphous RhPd alloy nanoparticles. As proof-of-concept applications, the obtained aRh nanoparticles are utilized as catalysts for hydrogenation of phenol and styrene oxide, exhibiting much higher catalytic activity than the crystalline Rh nanoparticles.